2017
DOI: 10.1002/cssc.201700180
|View full text |Cite
|
Sign up to set email alerts
|

Modified Fullerenes for Efficient Electron Transport Layer‐Free Perovskite/Fullerene Blend‐Based Solar Cells

Abstract: A variety of novel chemically modified fullerenes, showing different electron-accepting capabilities, has been synthesized and used to prepare electron transport layer (ETL)-free solar cells based on perovskite/fullerene blends. In particular, isoxazolino[60] fullerenes are proven to be a good candidate for processing blend films with CH NH PbI and obtaining enhanced power conversion efficiency (PCE) ETL-free perovskite solar cells (PSCs), improving the state-of-the-art PCE (i.e., 14.3 %) for this simplified d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 53 publications
1
70
1
Order By: Relevance
“…Methylammonium lead iodide perovskite (MAPI) solar cells constitute an emerging photovoltaic technology that in recent years has shown an outstanding improvement in power conversion efficiency, surpassing 21 % . However, despite this significant progress, poor stability of perovskite devices remains a major issue.…”
Section: Figurementioning
confidence: 99%
“…Methylammonium lead iodide perovskite (MAPI) solar cells constitute an emerging photovoltaic technology that in recent years has shown an outstanding improvement in power conversion efficiency, surpassing 21 % . However, despite this significant progress, poor stability of perovskite devices remains a major issue.…”
Section: Figurementioning
confidence: 99%
“…These layers are invaluable because they determine the polarity of the device,i mprove stability,p assivate surface charge traps,a nd aid in chargeextraction transport from the active layer to the electrodes ( Figure 1). [11] However,the ETM is limited mainly to fullerenes such as PC 61 BM and other derivatives, [12][13][14][15][16][17] and there are few examples of efficient non-fullerene inverted PSCs reported. Despite the lower PCE at present, the inverted planar devices, which are based on p-i-n configurations,a re attractive because the relatively simple device architecture is promising for flexible devices and is amenable to low-temperature and scalable fabrication techniques.…”
mentioning
confidence: 99%
“…Pascual et al deposited an MAPbI 3 :C 70 blend layer to fabricate ETL-free devices. [97] A highest PCE of 14.3% was demonstrated. As a result, the MAPbI 3 :C 70 based PSCs exhibited larger recombination resistance than the pristine MAPbI 3 based ones, showing a highest PCE of 13.6%.…”
Section: Effect Of Additivementioning
confidence: 88%
“…Xiao and co-workers reported robust inverted ETL-free PSCs, the device with Ti interlayer maintained nearly 90% and 77% of the initial PCE after 15 and 40 days, respectively, [109] which represents a significant device stability improvement with metal cathode directly in contact with perovskite layer. [97] In the work by Han et al, the photostability of the champion ETL-free devices without encapsulation was measured under continuous light soaking (1 sun) under ambient conditions (25% humidity, 25 °C), after 192 h of irradiation, the device remains >90% of its initial PCE, which is encouraging result for robust ETL-free PSC. [111] As for the photostability, Pascual and co-workers demonstrated that introducing C 70 into perovskite film significantly improves the photostability of ETL-free PSCs as the device suffered only about 10% PCE reduction after 3 h storage under continuous illumination.…”
Section: Stabilitymentioning
confidence: 98%